(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Informed consent has been implemented through a set of rules, at both national and international level, which protect individual autonomy as much as possible from paternalism, abuse, inducement, mistreatment, and deception. However, informed consent must not be merely understood as the outcome of a procedure for the transfer of information, however precise and detailed it may be. The article advocates its being rethought within a relational perspective, according to which not only the quantity or the quality of the information provided is at stake, but also the relational context within which this information is developed. The precondition for free and informed consent, besides the information received, is the relationship of trust between the parties involved, and the consistency between their modes of interaction and the need to maintain mutual trust. In that sense, the information is adequate and relevant not in itself, but as a function of the kind of relationship between the parties.